Factors Related to the Nutritional Status of Toddlers in the Manulai II District of Alak, Kupang City - Duwiri, Anjela Agustin; Picauly, Intje; Liufeto, Mega (Pergizi Pangan DPD NTT, 2025)
The nutritional status of toddlers greatly affects their health, growth, and development, because toddlerhood is a crucial age when growth and development occur rapidly. Therefore, nutritional deficiencies during this period can lead to malnutrition in toddlers. This study aims to determine the relationship between family food income, basic immunization status, medical history, history of exclusive breastfeeding, food, and nutritional status in toddlers in the working area of Manulai II Village, Alak District, Kupang City. The sample was determined using the Lemeshow formula with a sample size of 80 respondents. Statistical tests used Chi-square analysis with a=0.05. The results showed that the variables of Family Food Income (p-value=0.266), Basic Immunization Status (p-value=0.158), Medical History (p-value=0.461), and History of Exclusive Breastfeeding (p-value 0.101) were not related to the nutritional status of toddlers in the working area of Manulai II Village, Alak District, Kupang City. It is hoped that mothers of toddlers will pay attention to and increase their family food income, pay attention to the basic immunization status of their toddlers every day, and increase their knowledge about the importance of medical history and exclusive breastfeeding in order to prevent malnutrition in toddlers.